ESP distance learning methods At technical universities - Nadiia P. Vilkhovchenko (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
The paper focuses on the urgent problems of linguadidactics caused by Covid-19 pandemic and the need to implement online learning at all Ukrainian institutions of higher learning. English for Specific Purposes online learning involves modern methods that are constantly being improved. They are aimed at effective interaction of all participants in the learning process. The Department of Foreign Languages in Lviv polytechnic national university analyzed the feedback from the teaching staff and students concerning methods applied in online classes which were held during the quarantine period in 2020–2021. Observations of teaching experience, as well as the positive feedback from students proved that online learning English for specific purposes can be as effective as the offline one. The study considers a number of important principles that should be followed in order to succeed in distance learning. English for Specific Purposes online tools involved both synchronous and asynchronous methods. The former methods included videoconferences held with the help of various applications, e.g. Zoom, Microsoft Teams, Google Meet etc. Asynchronous means consisted of using instant messengers, email, educational platforms, i.e. virtual learning environment of the university based on the Moodle platform. We conducted a survey among students of five groups of different technical specialties. The survey aimed at finding out their opinion concerning effectiveness of ESP online lessons. It helped to discover what kind of difficulties the students had faced. The survey also allowed us to understand which types of activities were better perceived during video conferences in comparison with lessons in the classroom (i.e. listening and watching video). The analysis of the results obtained brought us to a conclusion about the most efficient way of conducting online classes. Thus, a combination of asynchronous and synchronous methods appeared to be the most effective tool for online mastering of ESP. On the one hand, the asynchronous method can be effective to consolidate lexical and grammar material, as well as develop reading skills. On the other hand, synchronous method provides direct communication in the «student-teacher» format and is the most effective means of transmission and acquiring new knowledge in the discipline of English for Specific Purposes. It also develops speaking skills while involving students in work with breakout rooms. The paper also discusses the issue of students’ knowledge and skills assessment. The process of control has become automated and, thus, more convenient. Diagnostic and control works were performed in the form of current and final tests, hosted on the Moodle platform (virtual learning environment of Lviv Polytechnic National University). This greatly facilitates teacher’s work; as such tests contain a convenient option of automatic checking the correctness of students’ answers to the tests.